Transformational health communication a new perspective on healthcare and prevention - Werder, Olaf ca. 20./21. Jh (Palgrave Macmillan, 2024)
Chapter 1: The Field of Health Communication: An Overview -- Chapter 2: A Failure to Communicate -- Chapter 3: Creatures of Habit – Automatic Health Behaviour -- Chapter 4: The Politics Of Talking Health: Power, Ethics, And Other Dilemmas -- Chapter 5: Eudaimonia – The Tricky Endeavour To Find Evidence for Wellbeing or its Absence -- Chapter 6: Culture’s Consequences – Making Health Communication More Equitable And Inclusive -- Chapter 7: Nurturing a Shared Vision: Self-identity, Relationship Building and People-powered Interventions -- Chapter 8: Hashtag Stay Healthy – Digital Media for Health Communication -- Chapter 9: Back To The Roots – Using Health Communication To Connect.